Land Policy and Land Market Activity in Kazakhstan - AITKHOZHAYEVA, Gulsim; TIREUOV, Kanat; PENTAYEV, Toleubek (Journal of Environmental Management and Tourism; Vol 10 No 3 (2019): JEMT Volume X Issue 3(35) Summer 2019, 2019)
The study seeks to determine agricultural land market functioning nowadays in Kazakhstan. The research presents views of experts on the land reforms, on land market functioning and its operating principles, identifies factors determining the development of land market, examines the opportunities for land market research, evaluates the development of agricultural land market development in Kazakhstan.